2018
DOI: 10.1016/j.agsy.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to improve sustainability on commercial pasture-based dairy farms by assessing environmental impact

Abstract: For pasture-based dairy farming to become more sustainable, the negative environmental impacts associated with milk production must be minimized. These negative impacts include eutrophication, ammonia emissions and greenhouse gas (GHG) emissions. Two tools, a nutrient budget and a carbon footprint calculator, allow farmlevel assessments of these negative impacts. In this study, a nutrient budget was used to calculate the efficiency of nitrogen and phosphorous use, and a carbon footprint calculator was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
1
10
1
1
Order By: Relevance
“…Methane emissions, as a result of enteric fermentation from dairy cows, ranged between 30% and 65% and comprised the highest contributor to the total GWP in the current study. The N0 and N20 treatment values are comparable to other literature values, which were between 58 and 65% of the total CO 2 eq in the CF of milk in dairy systems [ 6 , 53 , 55 , 56 , 57 ], but were found to be lower for the N60 and N80 treatments. However, most of these values were obtained from intensive confinement systems in which cows had a higher daily DM intake and consequently higher CH 4 emissions per cow and year.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Methane emissions, as a result of enteric fermentation from dairy cows, ranged between 30% and 65% and comprised the highest contributor to the total GWP in the current study. The N0 and N20 treatment values are comparable to other literature values, which were between 58 and 65% of the total CO 2 eq in the CF of milk in dairy systems [ 6 , 53 , 55 , 56 , 57 ], but were found to be lower for the N60 and N80 treatments. However, most of these values were obtained from intensive confinement systems in which cows had a higher daily DM intake and consequently higher CH 4 emissions per cow and year.…”
Section: Discussionsupporting
confidence: 84%
“…The calculated CF, from the investigated low-cost grazing system reported here, ranged between 1.3 and 2.6 kg CO 2 eq kg ECM −1 for South Africa ( Table 3 ). These values are higher than studies by Galloway et al (2018) [ 6 ] and Keller et al (2017) [ 51 ], which reported CF values in the range 0.94–2.07 kg CO 2 eq kg ECM −1 and 1.2–2.0 kg CO 2 eq kg raw milk, respectively, from pasture-based dairy systems. However, the CF of the N20 treatment was within this range (1.3 kg CO 2 eq kg ECM −1 ), and this is more representative of the normal management regime and fertilizer guidelines currently followed.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…When GHG emissions were allocated between these various purposes, Weiler et al ( 2014 ) found GHG emissions per unit weight of milk from smallholder dairying in Kenya of 2.0 (0.9–4.3) kg CO 2 ‐e using economic allocation to food products only, 1.6 (0.8–2.9) kg CO 2 ‐e when allocation was based on economic functions, and 1.1 (0.5–1.7) kg CO 2 ‐e when emissions allocation considered the livelihood values of livestock. These emissions intensities are comparable to intensive dairy production systems (Alvarez‐Hess et al, 2019 ; Beauchemin et al, 2010 ; Christie et al, 2018 ; Galloway et al, 2018 ), clearly highlighting a need for careful consideration of the diverse economic, environmental and socio‐economic roles that livestock play, particularly in smallholder systems.…”
Section: In Pursuit Of Multi‐scale Transdisciplinary Solutions: Conse...mentioning
confidence: 90%